Right to abortion and right to life: balancing the competing interests of the pregnant woman and the unborn child (foetus) (2016)
Abortion has become a perennial topic of discourse among legal philosophers, medical practitioners, moralists, feminists, religious activists and other stake holders. There have been conflicting opinions on whether or not abortion should be legalised or not. Whereas some schools of thought believe abortion should be liberalised, some are of the opinion that it should be strictly criminalised in order to protect the right to life of the unborn child/foetus. This paper seeks to review the two sides of the divide in order to come up with suggestions as to the best approaches to be adopted in balancing the rights of the pregnant woman and those of the foetus. The laws of some jurisdictions which are purposively selected are reviewed in order to sift out the best approaches to be adopted in balancing the conflicting interests of the pregnant woman and the foetus. It is concluded that no one's interest should jeopardise the rights of the other, but balancing the rights of the two based on relevant consideration of some salient factors will be appropriate.